Contrasting fast precipitation responses to tropospheric and stratospheric ozone forcing. Issue 3 (4th February 2016) - MacIntosh, C. R.; Allan, R. P.; Baker, L. H.; Bellouin, N.; Collins, W.; Mousavi, Z.; Shine, K. P.
Abstract: The precipitation response to radiative forcing (RF) can be decomposed into a fast precipitation response (FPR), which depends on the atmospheric component of RF, and a slow response, which depends on surface temperature change. We present the first detailed climate model study of the FPR due to tropospheric and stratospheric ozone changes. The FPR depends strongly on the altitude of ozone change. Increases below about 3 km cause a positive FPR; increases above cause a negative FPR. The FPR due to stratospheric ozone change is, per unit RF, about 3 times larger than that due to tropospheric ozone. As historical ozone trends in the troposphere and stratosphere are opposite in sign, so too are the FPRs. Simple climate model calculations of the time‐dependent total (fast and slow) precipitation change, indicate that ozone's contribution to precipitation change in 2011, compared to 1765, could exceed 50% of that due to CO2 change. Key Points: Fast precipitation response to ozone change simulated in a global climate model Fast precipitation responses to tropospheric and stratospheric O3 change oppose each other Simple model indicating present‐day precipitation change due to O3 could exceed 50% of that from CO2